1992
DOI: 10.1007/bf00497286
|View full text |Cite
|
Sign up to set email alerts
|

A review and update of animal toxicoses associated with fumonisin-contaminated feeds and production of fumonisins by Fusarium isolates

Abstract: During the 1989 corn harvest season, numerous reports of equine leukoencephalomalacia (ELEM) outbreaks and a pulmonary edema (PPE) syndrome in swine from several regions of the United States were received by the National Veterinary Services Laboratories (NVSL), Ames, Iowa. Previous and concurrent research linked Fusarium moniliforme and fumonisin-contaminated feeds to both diseases. Chemical and mycological investigations revealed fumonisin B1 (FB1) concentrations of 20 to 360 ppm in suspect swine feeds and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 16 publications
4
90
0
4
Order By: Relevance
“…The most important producers of fumonisins are F. verticillioides and F. proliferatum because of their overall high levels of production, wide geographical distribution, frequent occurrence on maize, and association with known animal mycotoxicoses (62,63). With the exception of F. verticillioides and F. proliferatum, less than 50% of isolates of other fumonisin-producing Fusarium species may produce fumonisins at various levels (51).…”
Section: Fumonisin Producersmentioning
confidence: 99%
“…The most important producers of fumonisins are F. verticillioides and F. proliferatum because of their overall high levels of production, wide geographical distribution, frequent occurrence on maize, and association with known animal mycotoxicoses (62,63). With the exception of F. verticillioides and F. proliferatum, less than 50% of isolates of other fumonisin-producing Fusarium species may produce fumonisins at various levels (51).…”
Section: Fumonisin Producersmentioning
confidence: 99%
“…Because FB1 reduces the uptake of folate in different cell lines, fumonisin consumption has been implicated in connection with neural tube defects in human babies (12,14). In addition, elevated levels of fumonisins in animal feed cause diseases such as equine leukoencephalomalacia (ELEM) in horses and porcine pulmonary edema (PPE) in swine (15). They have been shown to cause liver and kidney cancer in rats (9).…”
Section: Background On Fumonisin and Aflatoxin Standardsmentioning
confidence: 99%
“…In rural areas of Transkei, Southern Africa, FB1 and FB2 have been found in home-grown corn that produced and consumed by people whole living in there areas [10] . Fumonisin have also been found in feeds that were associated with ELEM that obtained from South Africa, the United States and Brazil [18,20,22,23] . Wilson et al have reported that the level of FB1 and FB2 were as high as 122 and 23 µg g −1 [23] .…”
Section: Occurrence Of Fumonisins In Foods and Feedsmentioning
confidence: 93%
“…Among the forms that have been characterized, are Fumonisin B1 (FB1), Fumonisin B2 (FB2) and fumon.isin B3 (FB3) (the B series of fumonisins) [14,17] . Fumonisin B1 is also known as macrofusin and the most abundant of the fumonisin family and usually accounts for 70-80% of the total fumonisin content of F. verticillioides cultures and naturally contaminated foods [18] (Fig. 2).…”
Section: Chemical and Physical Properties Of Fumonisinsmentioning
confidence: 99%